Setosphaeria turcica ATR turns off appressorium‐mediated maize infection and triggers melanin‐involved self‐protection in response to genotoxic stress - Zeng, Fanli (Mol Plant Pathol, 2020)
Eukaryotic organisms activate conserved signalling networks to maintain genomic stability in response to DNA genotoxic stresses. However, the coordination of this response pathway in fungal pathogens remains largely unknown. In the present study, we investigated the mechanism by which the northern corn leaf blight pathogen Setosphaeria turcica controls maize infection and activates self‐protection pathways in response to DNA genotoxic insults. Appressorium‐mediated maize infection by S. turcica was blocked by the S‐phase checkpoint. This repression was dependent on the checkpoint central kinase Ataxia Telangiectasia and Rad3 related (ATR), as inhibition of ATR activity or knockdown of the ATR gene recovered appressorium formation in the presence of genotoxic reagents. ATR promoted melanin biosynthesis in S. turcica as a defence response to stress. The melanin biosynthesis genes StPKS and StLac2 were induced by the ATR‐mediated S‐phase checkpoint. The responses to DNA genotoxic stress were conserved in a wide range of phytopathogenic fungi, including Cochliobolus heterostrophus, Cochliobolus carbonum, Alternaria solani, and Alternaria kikuchiana, which are known causal agents for plant diseases. We propose that in response to genotoxic stress, phytopathogenic fungi including S. turcica activate an ATR‐dependent pathway to suppress appressorium‐mediated infection and induce melanin‐related self‐protection in addition to conserved responses in eukaryotes.